Accessibility and Morphology of Cellulose Fibres Treated with Sodium Hydroxide - Chunyan Jiao; Jizhong Xiong (BioResources, 2014)
Cellulose fibres were treated with sodium hydroxide (NaOH) to improve the accessibility of chemical reagents and the roughness of fibre surface at low temperatures. The accessibility, supermolecular structure, morphology, and physical properties of fibres were investigated using solid-state cross polarisation/magic angle spinning 13C nuclear magnetic resonance (CP/MAS 13C NMR), wide-angle X-ray diffraction (WAXD), and scanning electron microscopy (SEM). The results showed that in low temperature (-16 °C), the iodine sorption value of cellulose fibres is 145.2 mg. The shift from the C6 signal of the molecular structure to the amorphous area indicated a decrease in the crystallinity of the material from 66% to 8%, and the transformation from cellulose I to II occurred. The SEM revealed fold shapes in the fibre surface, which increased the fibre surface area.